NRF3 activates mTORC1 arginine-dependently for cancer cell viability - Shuuhei Hirose; Tsuyoshi Waku; Misato Tani; Haruka Masuda; Keiko Endo; Sanae Ashitani; Iori Aketa; Hina Kitano; Sota Nakada; Ayaka Wada; Atsushi Hatanaka; Tsuyoshi Osawa; et al. (iScience, 2023)
Summary: Cancer cells coordinate the mTORC1 signals and the related metabolic pathways to robustly and rapidly grow in response to nutrient conditions. Although a CNC-family transcription factor NRF3 promotes cancer development, the biological relevance between NRF3 function and mTORC1 signals in cancer cells remains unknown. Hence, we showed that NRF3 contributes to cancer cell viability through mTORC1 activation in response to amino acids, particularly arginine. NRF3 induced SLC38A9 and RagC expression for the arginine-dependent mTORC1 recruitment onto lysosomes, and it also enhanced RAB5-mediated bulk macropinocytosis and SLC7A1-mediated selective transport for arginine loading into lysosomes. Besides, the inhibition of the NRF3–mTORC1 axis impaired mitochondrial function, leading to cancer cell apoptosis. Consistently, the aberrant upregulation of the axis caused tumor growth and poor prognosis. In conclusion, this study sheds light on the unique function of NRF3 in arginine-dependent mTORC1 activation and the pathophysiological aspects of the NRF3–mTORC1 axis in cancer development.